Laporan Kasus: Profil Hematologi Babi Landrace Usia 2 Bulan yang Mengalami Diare - Banggur, Mikael; Wuhan, Yustinus Oswin Primajuni (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2025)
Pigs are among the livestock commodities widely developed by farmers across various regions in Indonesia as sources of animal-based food. The overall health of livestock significantly influences productivity and the sustainability of farming operations. Hematological parameters serve as crucial indicators of physiological conditions and the health status of animals. Hematological examinations facilitate early detection of health issues, enabling prompt preventive or therapeutic interventions. In this case, a two-month-old female Landrace piglet exhibited signs of illness over a three-week period. The observed symptoms included diarrhea, reduced appetite and water intake, accompanied by weight loss during the illness. Hematological analysis revealed that the piglet was experiencing microcytic anemia due to iron deficiency, along with a decrease in white blood cell count attributed to intrinsic factors